2007
DOI: 10.1029/2006ja012186
|View full text |Cite
|
Sign up to set email alerts
|

Dual structure of auroral acceleration regions at substorm onsets as derived from auroral kilometric radiation spectra

Abstract: [1] Two sources of auroral kilometric radiation (AKR) and their development prior to and during substorms were identified from high-time-resolution spectrograms provided by Polar/PWI ac electric field observations and were investigated in connection with the auroral acceleration process. One source is a low-altitude source region corresponding to middle-frequency AKR (MF-AKR), and the other is a high-altitude source region corresponding to low-frequency AKR (LF-AKR). The former appears during the substorm grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 61 publications
(78 reference statements)
4
70
0
1
Order By: Relevance
“…Keiling et al [2008] presented that fluctuation of the photon flux observed by the Polar satellite had same periodicity as ground Pi2s. Morioka et al [2007] presented clear one-to-one correspondences between AKR breakup and Pi2 occurrence. They demonstrated that each appearance of the high-altitude AKR with sudden increase in power associated with the Pi2 pulsation.…”
Section: Akr Modulation and Global Pi2 Oscillationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Keiling et al [2008] presented that fluctuation of the photon flux observed by the Polar satellite had same periodicity as ground Pi2s. Morioka et al [2007] presented clear one-to-one correspondences between AKR breakup and Pi2 occurrence. They demonstrated that each appearance of the high-altitude AKR with sudden increase in power associated with the Pi2 pulsation.…”
Section: Akr Modulation and Global Pi2 Oscillationsmentioning
confidence: 99%
“…[37] AKR is believed to emanate from the beams of auroral electrons, which are accelerated by the parallel electric potential [e.g., Morioka et al, 2007]. The temporal relation between AKR modulation and ground Pi2 oscillations suggests a coherent fluctuation between the parallel electric field (d k ) and upward FAC of the SCW (dj k ).…”
Section: Akr Modulation and Global Pi2 Oscillationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] AKR has been studied in relation to auroral breakup and auroral particle acceleration [e.g., Gurnett, 1974;Kaiser and Alexander, 1977;Fairfield et al, 1999] and is widely accepted to be generated by rapidly accelerated electrons accompanying sudden auroral activation in the polar magnetosphere [e.g., Anderson et al, 1998;Strangeway et al, 2001;Morioka et al, 2007]. Figure 2 shows the frequency-time spectrogram (f-t diagrams) of AKR observed by GEOTAIL and AL/AU index on 5 December 1995.…”
Section: Two Types Of Akrmentioning
confidence: 99%